Essays on agricultural and environmental economics - Silva, João Vitor Borges Gouveia da (2025)
Chapter 1: The Impact of Institutional Demarcation of Agricultural Fron tiers on Natural Land Use: the case of Matopiba This paper examines the impact of the institutionalization of Matopiba on natu ral land use dynamics in municipalities covered by Decree 8477/2015. To do so, we employ a Difference-in-Differences (DiD) framework, defining treatment and control groups based on the boundaries of this agricultural frontier. Our results highlight the environmental consequences of legally formalizing Brazil’s newest agricultural frontier. We find that municipalities within Matopiba experienced a differential decrease of 1.5% in natural land cover compared to municipalities located just outside its boundaries. Additionally, in terms of forest conversions, the institutional demarcation led to a 1.7% increase in total deforestation within Matopiba municipalities relative to non-Matopiba municipalities. Furthermore, when assessing the economic effects of the institutional framework, our findings suggest that Matopiba acts as a driver of regional economic growth, as the gross value added (GVA) per capita in Matopiba municipalities grew 19% more than in non-Matopiba municipalities. These results underscore the need for public poli cies that balance the agricultural expansion of Matopiba with the conservation of the Cerrado biome. Chapter 2: The 2021 Amazon River Flood: Effects on the Agricultural Econ omy of Amazonas Municipalities. This paper examines the impact of the 2021 Amazon River flood on agriculture economy of municipalities within the state of Amazonas. Using a Difference in-Differences (DiD) approach, we define municipalities crossed by the Amazon River in Amazonas as the treatment group and estimate the flood’s effects on agricultural outcomes. Our results indicate a significant reduction in agricultural production following the flood. Compared to municipalities outside Amazonas, the flooding led to a 23% to 33% decline in harvested area, crop production, and production value within affected municipalities. Additionally, when analyzing crop-specific effects, we find that corn, pineapple, and cocoa were the most im pacted, with estimated losses of 81%, 65%, and 45% in gross production value, respectively, after the 2021 flood. This findings should reorient the public policies towards the mitigation of adverse effects and anticipation of such events in order to avoid reductions in production and shortages in food supply in the region.